Shifting Cultivation within Bangladesh: An Overview - M. A. Hossain (Current Research Progress in Agricultural Sciences Vol. 3, 2024)
Land systems are a key entry point for policies to achieve progress towards the triple challenge of biodiversity conservation, climate change mitigation and human well-being. One important land system is shifting cultivation. Shifting cultivation remains an important land system in many tropical landscapes, but transitions away from shifting cultivation are increasingly common. In resource-poor communities, shifting agriculture involves alternating between cultivating and leaving a portion of land fallow. The bulk of indigenous households rely on shifting agriculture practices for subsistence living, employing millions of people. The need for more food and the growing number of shifting cultivators have caused this practice to change in the modern era. Like its neighbors, Bangladesh features hills that are degraded as a result of deforestation exacerbated by shifting agriculture. There has been a continuous debate on shifting cultivation. Soil erosion is to a large extent in Chittagong Hill Tracts (CHT) due to faulty cultivation in hill slopes, shifting cultivation, change in land use and reduction of land cover. This paper provides a review of shifting cultivation practices in the world with reference to Bangladesh, with an insight into emerging land use transition, its impacts and future priorities. Our review analysis shows that shifting cultivation transitions are diverse in themselves, in their drivers and their consequences. This calls for a critical and contextualised appraisal of the continuation of shifting cultivation, as well as, the transition away from it when designing land system policies that work for people and nature.